Key technologies and solutions of 5G high-speed railway wireless network - Yanhong JIAO; Tao WANG; Fuqiang LI; Xiangchen MA; Wenbin YAO (Dianxin kexue)
High-speed railway has become a part of daily life.It is very important to provide high-quality mobile communication network for high-speed railway users in 5G era.The technical challenges faced by high-speed railway construction after entering the 5G era were analyzed,and on this basis,the key technologies of 5G high-speed railway network,equipment selection,transmission resource demand analysis were analyzed and solutions were put forward.Based on the above technical analysis,combined with the actual network construction demand,construction scenarios,current network conditions and investment,5G high-speed railway wireless network construction scheme could be formulated accurately and efficiently according to local conditions.